Intraoperative cholangiogram during laparoscopic cholecystectomy: A clinical trial in rural setting. (17th April 2016) - Verma, Shreya; Wichmann, Matthias W.; Gunning, Thomas; Beukes, Eben; Maddern, Guy
Abstract: Objective: The routine use of intraoperative cholangiogram (IOC) in laparoscopic cholecystectomy (LC) remains a contentious issue. IOC helps to delineate biliary tree anatomy, prevent bile duct injury and image stones in the common bile duct (CBD). It may prove to be a valuable alternative to ERCP or MRCP, especially in the rural setting with limited resources. Design/Setting/Participants/Interventions/Main outcome measures: All patients undergoing laparoscopic cholecystectomy during a 12‐month period were audited. For the first 6 months, patients were recruited for routine IOC and for the second 6 months, routine IOC was not performed. Cases were analysed with regard to patient demographics, operative details and clinical outcomes. Results: A total of 75 patients were analysed within the 12‐month period. The majority were women aged 41–50. Ultrasound suggested common bile duct stones in 6.7% of cases. IOC was attempted in 50.7% of cases. Of these, 29 (76.3%) were successful. IOC added an average of 28 min to total theatre time. A total of 75% (n = 22) of IOCs showed normal flow of contrast into the intra‐ and extra‐hepatic biliary systems. In 17% (n = 5) of patients, stones within the CBD were suspected, and these were referred for further management. ERCP/MRCP confirmed CBD stones in 60% (n = 3) of these patients. There was poor correlation between pre‐operative suspicion and confirmed CBD stones (two patients only with pre‐operative suspected CBD stone confirmed on IOC and ERCP). There were no operative complications related to IOC. There were no post‐operative complications in cases where no IOC was done. Conclusion: The majority of patients treated in our centre were women, middle‐aged patients booked for elective laparoscopic cholecystectomy. Although only 6.7% cases were suspicious for CBD stones pre‐operatively, a total of 17% of patients with routine IOC suggested CBD stones. IOC was found to be safe, taking only an additional 28 min of total theatre time. Routine rather than selective use of IOC could be considered to improve patient safety and long‐term results.